Multistrategic Approaches in the Treatment of Acute Migraine During Pregnancy: The Effectiveness of Physiotherapy, Exercise, and Relaxation Techniques - Özge Baykan Çopuroğlu; Mehmet Çopuroğlu (Medicina)
Background and Objectives: Migraine is a common neurological condition that significantly impacts quality of life, especially in women during their reproductive years. Pregnancy poses unique challenges for migraine management due to hormonal changes and the limited use of pharmacological treatments. Non-pharmacological interventions, such as physiotherapy, exercise, and relaxation techniques, offer promising alternatives for managing migraines during this critical period. This study aims to evaluate the effectiveness of physiotherapy, structured exercise, and relaxation techniques in reducing migraine frequency, severity, and duration while improving psychosocial outcomes such as quality of life, stress levels, and sleep quality in pregnant women. Materials and Methods: Sixty pregnant women diagnosed with acute migraine were randomly assigned into three intervention groups: physiotherapy, structured exercise, and relaxation techniques. Each intervention lasted 8 weeks. The primary outcomes included migraine frequency, severity (measured by VAS), and duration. The secondary outcomes included quality of life (SF-36), stress (PSS), and sleep quality (PSQI). Statistical analyses were conducted using one-way ANOVA and paired t-tests. Results: All interventions significantly reduced migraine frequency, severity, and duration (p < 0.05). Physiotherapy demonstrated the greatest reduction in migraine frequency (45%) and severity (36%), while exercise yielded the most significant improvement in duration (42%). Relaxation techniques were particularly effective in reducing stress and anxiety levels. Quality of life and sleep quality improved across all groups, with unique benefits observed for each intervention. Conclusions: Physiotherapy, structured exercise, and relaxation techniques are effective, safe, and non-invasive interventions for managing acute migraines during pregnancy. These findings provide evidence-based alternatives to pharmacological treatments, highlighting the importance of holistic approaches to migraine management during pregnancy. Further research is needed to confirm long-term efficacy and explore combined interventions.